RESPON TANAMAN SELADA (Lactuca sativa L) TERHADAP PEMBERIAN PUPUK ORGANIK CAIR ASAL SAMPAH ORGANIK PASAR - Novriani, Novriani (Universitas Muhammadiyah Palembang, 2014)
This study aimed to determine the effect of liquid organic fertilizer (POC) organic waste and acquire POC concentration of organic waste is best for the growth and yield of lettuce. The study was conducted implemented in the Banuayu Village Buay Pemuka Peliung sub district, Ogan Komering Ulu district. Implementation period from February to April 2014. This study used non factorial completely randomized design, with 6 treatments and 4 replications group in order to get 24 plot experimental unit. The treatments used, namely; P0 (POC Market), P1 (POC 10 ml / liter of water), P2 (POC 20 ml / liter of water), P3 (POC 30 ml / liter of water), P4 (POC 40 ml / liter of water) and P5 (POC 50 ml / liter of water). The observed variables are plant height, number of leaves, canopy wet weight, shoot dry weight, root number, root fresh weight, root dry weight and plant weight. Giving POC can increase growth and yield of lettuce. Treatment P2 (POC 20 ml / liter of water) is the best treatment that can improve the growth and production of lettuce in terms of the mean look of the results obtained at the variable plant height (41.47 cm), number of leaves (10.5 strands), weight wet canopy (9.8 g), shoot dry weight (1.85 g), the number of roots (30.33 strands), root fresh weight (6.5 g) and root dry weight (1.41 g) and increased production the plant fresh weight (16.3 g) when converted the lettuce crop production for one hectare of 2.6 tonnes / ha.